Interpersonal and relational comminication - Watson, Kittie W.; Barker, Larry L. (Arizona: Gorsuch scarisbrick, 1990)
Contents: 1. introduction to interpersonal communication, 2. perceiving the self and other, 3. the self: intrapersonal communication processes, 4. processing messages: verbal communication, 5. processing nonverbal communication, 6.Listening and giving feedback, 7. foundation for relating interpersonally, 8. defining relationship: development and disengagement, 9.Intimate relationships, 10. family relationships, 11. work relationships.
Glosary p.363-383 Index p.385
Keywords: Comunicación Interpersonal